EFEK STIMULASI MOTOR POINT DENGAN BEKAM BASAH TERHADAP TEKANAN DARAH SISTOLIK DAN DIASTOLIK PADA WANITA HIPERTENSI - Tulus Puji Hastuti; Budi Ekanto Ekanto; Poltekes Kemenkes Semarang (Jurnal Ilmiah Kesehatan Keperawatan, 2013)
Increased systolic and diastolic blood pressure may occur as a result of increased peripheral vascular resistance. Various efforts in the management of patients with hypertension has been done is a medical and complementary alternative medicine. Complementary alternative medicine : cupping method is not new among the people of Indonesia. Cupping make better microcirculation blood vessels causing a relaxing effect on the muscles so that it can lower blood pressure. Cupping works by stimulating or activating blood vessel dilation. This study aimed to examine the effect of cupping therapy to decrease systolic blood pressure and diastolic blood pressure. Research methodology is first day measurements Systolic and Diastolic blood pressure, further action on the Wet Cupping: hump, shoulders, shoulder blades kedu. Seven days measurement Systolic and Diastolic blood pressure, further action on the Wet Cupping: hump, shoulders, shoulder blades. The mean systolic blood pressure measurements were compared with the first day to the seventh day of the measurement results (7), further analysis using paired t-test when the data distribution is normal, if not normal Wilcoxon test was used alternative. Conclusions from the analysis showed that systolic blood pressure after wet cupping on the hump, both shoulder blades and both lower than 20 mmHg systolic blood pressure before wet cupping. Diastolic blood pressure after wet cupping on the hump, both shoulder blades and both lower than 13 mmHg diastolic blood pressure before wet cupping.   Keywords: cupping, systolic, diastolic